Case report: A case of severe capecitabine toxicity due to confirmed in trans compound heterozygosity of a common and rare DPYD variant - de Haar-Holleman, Amy; Cortoos, Pieter-Jan; Vlaeminck, Jelle; Van Landuyt, Paulien; Steurbaut, Stephane; Vaeyens, Freya; Haufroid, Vincent (Frontiers in Pharmacology, 2024)
Variations in the activity of the enzyme dihydropyrimidine dehydrogenase (DPD) are associated with toxicity to fluoropyrimidine-containing chemotherapy. Testing of DPD deficiency either by targeted genotyping of the corresponding DPYD gene or by quantification of plasma concentration of uracil and dihydrouracil (phenotyping approach) are the two main methods capable of predicting reduced enzymatic activity in order to reduce adverse reactions after fluoropyrimidine treatment. In this paper, we describe a patient with locally advanced colon carcinoma with severe toxicity following capecitabine therapy. Whereas targeted genotyping for the 4 most common DPYD variants analysis revealed heterozygous presence of the c.2846A>T variant, which is a relatively common variant associated with a partial deficiency, additional phenotyping was compatible with a complete DPD deficiency. Subsequent sequencing of the whole DPYD gene revealed the additional presence of the rare c.2872A>G variant, which is associated with a total loss of DPD activity. A clinical case of in trans compound heterozygosity of a common and a rare DPYD variant (c.2846A>T and c.2872A>G) has, to the best of our knowledge, not been previously described. Our case report shows the importance of performing either preemptive phenotyping or preemptive complete genetic analysis of the DPYD gene for patients planned for systemic fluoropyrimidines to identify rare and low frequency variants responsible for potentially life-threatening toxic reactions.